Efficacy and safety of fosaprepitant in the prevention of nausea and vomiting following highly emetogenic chemotherapy in Chinese people: A randomized, double‐blind, phase III study. (10th April 2017) - Yang, L.Q.; Sun, X.C.; Qin, S.K.; Cheng, Y.; Shi, J.H.; Chen, Z.D.; Wang, Q.M.; Zhang, H.L.; Hu, B.; Liu, B.; Zhang, Q.Y.; Wu, Q.; et al.
Abstract : The prevention of chemotherapy‐induced nausea and vomiting was one of the most challenging supportive care issues in oncology, especially to highly emetogenic chemotherapy (HEC). A total of 645 patients were randomized into fosaprepitant group (fosaprepitant/placebo 150 mg d1 in combination with granisetron and dexamethasone) or aprepitant group (aprepitant/placebo 125 mg d1; 80 mg d2‐d3 plus granisetron and dexamethasone).The primary endpoint was the percentage of patients who had a complete response (CR) over the entire treatment course (0–120 hr, overall phase [OP]). It was assessed by using a non‐inferiority model, with a non‐inferiority margin of 10%. The difference of the CR rate was compared between two groups with chi‐square analysis. Six hundred and twenty‐six patients were included in the per protocol analysis. The percentage of patients with a CR in the fosaprepitant group was not inferior to that in the aprepitant group (90.85% versus 94.17%, p  =   .1302) during OP. Whether the cisplatin‐based chemotherapy or not, the CR rate of the fosaprepitant group was not inferior to that of the aprepitant group. Both regimens were well tolerated. The most common adverse event was constipation. Fosaprepitant provided effective and well‐tolerated control of nausea and vomiting associated with HEC in Chinese patients.